Evaluasi Peresepan Obat Antihipertensi Pada Pasien Hipertensi Di Apotek Afina Periode Juli – Desember 2021 - Hastuti, Dwi (Program Studi Farmasi UNAJA, 2022)
Abstract Background: Hypertension is a disease with the highest mortality rate in the world. Hypertension has non-specific symptoms so it is often referred to as the silent killer, therefore it is necessary to evaluate the prescription of antihypertensive drugs. Objective: . To evaluate the use of antihypertensive drugs at the Apotek Afina, Yogyakarta by reviewing the indicators of the right patient, the right indication, the right drug, and the right dose. Method: Descriptive observational method with retrospective data collection. The sampling technique was random sampling. The data to be studied uses prescription data and medical records from hypertensive patients at the Afina Pharmacy in July-December 2021 with a total of 90 patients. The data obtained were then evaluated for rationality by calculating the percentage of the right indication, the right patient, the right drug, and the right dose Results: The results showed that the most common comorbidity suffered was diabetes mellitus (41.1%), the most use of antihypertensive drugs is the CCB group (43.22%), the single drug therapy was used in 60 medical patients (66.67%) and combination therapy in 30 medical records (33.33%). Conclusion: Evaluation of the use of antihypertensive drugs at the Afina Pharmacy for the period July - December 2021 obtained 100% correct patients, 100% correct indications, 100% correct drugs, 100% correct dosages